Reducing poverty and hunger through food policy research: Highlights IFPRI and DFID partnership - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
For more than 40 years, the International Food Policy Research Institute (IFPRI) has been providing cutting-edge research and policy options on food and nutrition security to partners in donor and recipient countries around the world. IFPRI’s partners in the United Kingdom have played an especially critical role, with the Department for International Development (DFID) serving as a generous and dependable donor and partner to IFPRI since 1984.